Increasing risks of the explosive extratropical cyclones over the North Atlantic storm track: a perspective from their surface wind maxima - Shen-Ming Fu; Hui Ma; Li-Zhi Jiang (Environmental Research Letters, 2024)
Extratropical cyclones play a crucial role in balancing the global momentum, energy, and moisture, and also, they shape the extreme weather events over the extra-tropics. As the strongest category of the extratropical cyclones, the explosive extratropical cyclones (EECs) frequently induce severe disasters through their strong surface winds. During the entire lifespan of an EEC, there is a maximum value of its surface wind (i.e. the maximum surface wind; MSW), which processes the greatest destructive power. After nearly a century of research on the EECs, key features about their MSWs still remain vague. In this study, we systematically investigate the EECs’ MSWs over the North Atlantic storm track (NAST) based on the ERA-Interim reanalysis. It is found that, the average intensity of EECs’ MSWs shows a significant increasing trend of ∼0.3 m s ^−1 per 10a. More importantly, for the last 20 years, even larger increasing rates of 1.5 m s ^−1 and 3.5 m s ^−1 per 10a are found in the average and maximum intensities of the EECs’ MSWs, respectively, implying the EECs’ risks increase notably for the NAST. We further clarify the physical mechanisms governing the production of EECs’ MSWs, and then establish a mechanism-based statistical model, which has the potential to predict the MSWs’ annual average intensity. In summary, our study fills a knowledge gap for the EECs’ MSWs, which would have broad implication of the economics and society.